WEBVTT
00:00:01.200 --> 00:00:05.730
In this video, weβll learn how to express complex numbers in exponential form.
00:00:06.270 --> 00:00:10.050
We should know how to express a complex number in algebraic and polar form.
00:00:10.290 --> 00:00:12.810
So this is a natural extension of this logic.
00:00:13.220 --> 00:00:18.640
Weβll learn what we mean by exponential form and how to multiply and divide with these numbers.
00:00:18.920 --> 00:00:29.520
Weβll also learn how to convert between numbers in algebraic, polar, and exponential form before discovering how the exponential form can help us solve equations involving complex numbers.
00:00:30.450 --> 00:00:35.140
The algebraic form of a complex number is π§ equals π plus ππ.
00:00:35.700 --> 00:00:38.060
π and π are real numbers.
00:00:38.420 --> 00:00:44.160
And we say that π is the real part of the complex number, whereas π is the imaginary part.
00:00:44.530 --> 00:00:50.880
And we know that the polar β sometimes called trigonometric form of a complex number β is π cos π plus π sin π.
00:00:51.370 --> 00:00:55.620
π is the modulus and π is the argument usually given in radians.
00:00:55.940 --> 00:00:59.150
So what about the exponential form of a complex number?
00:00:59.500 --> 00:01:01.360
Here, we need Eulerβs formula.
00:01:01.660 --> 00:01:06.510
This says that π to the ππ is equal to cos π plus π sin π.
00:01:06.700 --> 00:01:09.590
Now, letβs compare this to the polar form of a complex number.
00:01:09.980 --> 00:01:17.390
We can see that if we multiply through by π, we get ππ to the ππ equals π cos π plus π sin π.
00:01:17.590 --> 00:01:25.730
And so, we can write our complex number π§ as ππ to the ππ, where π is still the modulus and π is still the argument, given in radians here.
00:01:26.110 --> 00:01:35.280
And we can use the same methods for calculating the modulus and argument of a complex number in exponential form as we would for a complex number written in polar form.
00:01:35.870 --> 00:01:37.370
Letβs see what this might look like.
00:01:38.400 --> 00:01:45.210
Put the number π§ equals five root two over two minus five root six over two π in exponential form.
00:01:45.620 --> 00:01:48.420
This complex number is currently in algebraic form.
00:01:48.660 --> 00:01:54.720
It has a real part of five root two over two and an imaginary part of negative five root six over two.
00:01:55.130 --> 00:02:03.640
Remember a complex number in exponential form is ππ to the ππ, where π is the modulus and π is the argument in radians.
00:02:04.160 --> 00:02:07.130
The modulus is fairly straightforward to calculate.
00:02:07.300 --> 00:02:13.940
For a complex number of the form π plus ππ, its modulus is the square root of the sum of the square of π and π.
00:02:14.400 --> 00:02:21.320
In this case, itβs the square root of five root two over two all squared plus negative five root six over two all squared.
00:02:21.720 --> 00:02:25.860
Five root two over two all squared is 25 over two.
00:02:26.030 --> 00:02:30.420
And negative five root six over two all squared is 75 over two.
00:02:30.710 --> 00:02:37.360
The sum of 25 over two and 75 over two is 100 over two, which is simply 50.
00:02:37.460 --> 00:02:42.590
So the modulus of π§ is the square root of 50, which we can simplify to five root two.
00:02:43.180 --> 00:02:44.730
But what about the argument?
00:02:44.940 --> 00:02:54.470
If we put this complex number on the Argand plane, itβs represented by the point whose Cartesian coordinates are five root two over two and negative five root six over two.
00:02:54.770 --> 00:02:57.190
This means it lies in the fourth quadrant.
00:02:57.610 --> 00:03:09.460
We can find the argument for complex numbers that lie in the first and fourth quadrant by using the formula arctan of π divided by π or arctan of the imaginary part divided by the real part.
00:03:09.770 --> 00:03:17.830
In this example, thatβs arctan of negative five root six over two divided by five root two over two, which is negative π by three.
00:03:18.130 --> 00:03:21.080
So the argument for our complex number is negative π by three.
00:03:21.510 --> 00:03:26.800
We calculated the modulus of π§ to π five root two and its argument to be negative π by three.
00:03:27.190 --> 00:03:32.310
So in exponential form, we can say itβs five root two π to the negative π by three π.
00:03:32.840 --> 00:03:37.600
And at this point, itβs worth recalling that the argument is periodic with a period of two π.
00:03:37.960 --> 00:03:41.380
So we can add or subtract multiples of two π to our argument.
00:03:41.550 --> 00:03:47.740
If we add two π to negative π by three, we get five root two π to the five π over three π.
00:03:48.500 --> 00:04:00.720
Whilst the argument of the complex number in this second form is outside of the range for the principal argument which is greater than negative π and less than or equal to π, itβs not unusual to see these numbers written in either form.
00:04:01.300 --> 00:04:04.900
And what about converting back from a number in exponential form?
00:04:05.290 --> 00:04:12.410
Well, the conversion between exponential and polar form is fairly straightforward, which is to use the same values for the modulus and the argument.
00:04:12.550 --> 00:04:20.430
To convert from exponential form back into algebraic form though, we first convert into polar form and then convert it to algebraic form.
00:04:20.750 --> 00:04:31.010
Since ππ to the ππ is the same as π cos π plus π sin π, we can distribute these parentheses and then compare this directly to the algebraic form of a complex number.
00:04:31.310 --> 00:04:36.190
The real part will be π cos π and the imaginary part will be π sin π.
00:04:36.720 --> 00:04:44.610
Now that we have a definition of the exponential form for a complex number, we can use this to develop some rules for multiplication and division with these numbers.
00:04:45.120 --> 00:04:51.790
Letβs say we have two complex numbers π one π to the ππ one and π two π to the ππ two.
00:04:52.270 --> 00:04:58.780
Their product is π one π to the ππ one multiplied by π two π to the ππ two.
00:04:59.230 --> 00:05:02.940
And then, we recall the properties of the modulus and arguments of a complex number.
00:05:03.240 --> 00:05:12.660
The modulus of the product of two complex numbers is equal to the product of their moduli and the argument of their product is equal to the sum of their respective arguments.
00:05:12.840 --> 00:05:19.740
So we can say that the product of π§ one and π§ two is π one π two π to the π π one plus π two.
00:05:20.330 --> 00:05:24.560
Essentially, we multiply their moduli and add their arguments.
00:05:24.760 --> 00:05:33.160
Similarly, to divide two complex numbers, we get π one divided by π two multiplied by π to the π π one minus π two.
00:05:33.500 --> 00:05:37.400
This time, we divide their moduli and subtract their arguments.
00:05:37.970 --> 00:05:47.910
Now whilst it does look like we could have simply applied the rules for integer exponents to derive these results, we do need to be a little careful assuming those rules work for all complex numbers.
00:05:48.160 --> 00:05:50.220
This is not always necessarily true.
00:05:50.460 --> 00:05:57.040
And so, itβs much more preferable to think about the product and quotient of complex numbers in terms of their moduli and arguments.
00:05:57.580 --> 00:06:03.350
Letβs look at how to apply these processes to multiplication and division of complex numbers in exponential form.
00:06:04.310 --> 00:06:15.430
Given π§ one equals five π to the negative π by two π and π§ two equals six π to the π by three π, express π§ one π§ two in the form π plus ππ.
00:06:15.730 --> 00:06:22.910
Here, weβve been given two complex numbers in exponential form and weβre being asked to find their product in algebraic form.
00:06:23.270 --> 00:06:27.620
Itβs much simpler to multiply complex numbers whilst they are in exponential form.
00:06:27.960 --> 00:06:32.510
So weβll do that bit first before converting their product to algebraic form.
00:06:33.000 --> 00:06:39.360
To multiply two complex numbers in exponential form, we multiply their moduli and add their arguments.
00:06:39.550 --> 00:06:44.810
The modulus of our first complex number is five and its argument is negative π by two.
00:06:45.200 --> 00:06:49.450
The modulus of our second complex number is six and its argument is π by three.
00:06:49.940 --> 00:06:55.730
This means the modulus of the product of these two complex numbers will be five times six which is 30.
00:06:56.140 --> 00:07:00.590
And the argument of π§ one π§ two will be negative π by two plus π by three.
00:07:01.000 --> 00:07:04.330
We can add these two fractions by creating a common denominator.
00:07:04.390 --> 00:07:05.190
Thatβs six.
00:07:05.320 --> 00:07:10.660
And we get negative three π by six plus two π by six which is negative π by six.
00:07:10.760 --> 00:07:16.570
And therefore, we see that π§ one π§ two is 30π to the negative π by six π.
00:07:16.910 --> 00:07:18.190
And thatβs in exponential form.
00:07:18.370 --> 00:07:20.640
So how do we convert this into algebraic form?
00:07:20.950 --> 00:07:24.230
The easiest way is to represent it in polar form first.
00:07:24.260 --> 00:07:28.760
Itβs 30 cos negative π by six plus π sin of negative π by six.
00:07:28.910 --> 00:07:30.560
Weβll distribute these parentheses.
00:07:30.560 --> 00:07:37.030
And we see that this is equivalent to 30 cos of negative π by six plus 30 sin of negative π by six π.
00:07:37.370 --> 00:07:39.020
Now, these are standard results.
00:07:39.090 --> 00:07:46.500
Cos of negative π by six is root three over two and sin of negative π by six is negative one-half.
00:07:46.670 --> 00:07:54.280
And we can therefore see that π§ one π§ two β the product of these two complex numbers β simplifies to 15 root three minus 15π.
00:07:54.520 --> 00:07:57.060
This is now in algebraic form as required.
00:07:57.270 --> 00:08:03.910
If we compare it to the general form in our question, we see that π is 15 root three and π is negative 15.
00:08:05.610 --> 00:08:10.680
Given that π§ equals π root two over one minus π, write π§ in exponential form.
00:08:11.310 --> 00:08:13.560
To answer this question, we have two options.
00:08:13.640 --> 00:08:16.750
We could divide these two complex numbers in algebraic form.
00:08:16.960 --> 00:08:25.070
And to do this, we need to multiply both the numerator and denominator by the conjugate of the denominator then distribute and simplify as far as possible.
00:08:25.240 --> 00:08:27.860
Iβm sure youβll agree thatβs rather a lengthy process.
00:08:28.040 --> 00:08:31.240
Instead, weβll choose to write these complex numbers in exponential form.
00:08:31.540 --> 00:08:34.470
So weβll need to calculate their moduli and arguments.
00:08:34.920 --> 00:08:37.710
π root two is a purely imaginary number.
00:08:38.150 --> 00:08:43.130
On an Argand diagram, itβs represented by the point whose Cartesian coordinates are zero, root two.
00:08:43.590 --> 00:08:47.590
Its modulus is the length of the line segment that joins this point to the origin.
00:08:47.650 --> 00:08:48.510
So itβs root two.
00:08:48.910 --> 00:08:57.540
And since the argument is measured in the counterclockwise direction from the positive real axis, we can see that the argument of this complex number is equivalent to 90 degrees.
00:08:57.660 --> 00:08:59.170
Thatβs π by two radians.
00:08:59.330 --> 00:09:04.350
And in exponential form, we can say that this is the same as root two π to the π by two π.
00:09:04.850 --> 00:09:07.630
The complex number one minus π is a little more tricky.
00:09:07.780 --> 00:09:11.010
Its real part is positive and its imaginary part is negative.
00:09:11.010 --> 00:09:12.650
So it lies in the fourth quadrant.
00:09:12.850 --> 00:09:15.390
Now, its modulus is independent of this fact.
00:09:15.470 --> 00:09:21.360
We simply use the formula the square root of the sum of the square of the real and imaginary parts.
00:09:21.450 --> 00:09:26.630
So thatβs the square root of one squared plus negative one squared which once again is the square root of two.
00:09:26.760 --> 00:09:29.230
We do need to be a little bit more careful with the argument.
00:09:29.370 --> 00:09:36.230
Since itβs in the fourth quadrant, we can use the formula thatβs unique to complex numbers that are plotted in the first and fourth quadrants.
00:09:36.310 --> 00:09:41.290
Thatβs arctan of π over π, arctan of the imaginary part divided by the real part.
00:09:41.450 --> 00:09:46.240
So in this case, thatβs the arctan of negative one over one which is negative π by four.
00:09:46.510 --> 00:09:52.340
We expected a negative value for the argument as this time weβre measuring in a clockwise direction.
00:09:52.730 --> 00:10:00.170
And so, we can rewrite our fraction as root two π to the π by two π over root two π to the negative π by four π.
00:10:00.490 --> 00:10:02.120
And now, we can easily divide.
00:10:02.500 --> 00:10:07.640
To divide complex numbers in exponential form, we divide their moduli and subtract their arguments.
00:10:07.850 --> 00:10:14.100
Root two divided by root two is one and π by two minus negative π by four is three π by four.
00:10:14.390 --> 00:10:18.740
In exponential form then, π§ is equal to π to the three π by four π.
00:10:20.190 --> 00:10:23.830
Weβve seen how to multiply and divide with complex numbers in exponential form.
00:10:24.270 --> 00:10:29.290
Letβs now look at how to use properties of complex numbers in exponential form to solve equations.
00:10:30.130 --> 00:10:43.010
Given that ππ to the ππ plus ππ to the negative two ππ is equal to cos of two π minus five π sin of two π, where π is a real number and π is a real number, find π and π.
00:10:43.370 --> 00:10:47.680
Here, we have an equation formed of complex numbers, for which we have some unknowns.
00:10:47.790 --> 00:10:52.470
Before we can solve for π and π, weβll need to ensure that each complex number is in the same form.
00:10:52.930 --> 00:10:55.390
Letβs convert the left-hand side to polar form.
00:10:55.600 --> 00:10:57.600
Itβs made up of two complex numbers.
00:10:57.740 --> 00:11:00.250
Their moduli are π and π, respectively.
00:11:00.300 --> 00:11:03.520
And their arguments are two π and negative two π.
00:11:03.810 --> 00:11:12.720
So we can say that their sum is equal to π cos two π plus π sin two π plus π cos of negative two π plus π sin of negative two π.
00:11:13.040 --> 00:11:17.520
Now, weβre going to use the fact that cos π is an even function and sin π is an odd function.
00:11:17.730 --> 00:11:21.160
And this means that cos of negative two π is the same as cos of two π.
00:11:21.350 --> 00:11:25.460
But sin of negative two π is the same as negative sin of two π.
00:11:25.780 --> 00:11:29.070
And we can rewrite our equation ever so slightly as shown.
00:11:29.620 --> 00:11:33.230
We need to distribute π and π over their respective parentheses.
00:11:33.390 --> 00:11:34.920
And then, we collect like terms.
00:11:34.970 --> 00:11:40.920
And we see that we get cos of two π times π plus π plus π sin two π of π minus π.
00:11:41.270 --> 00:11:47.630
And of course, comparing this to original equation, we see that this is equal to cos of two π minus five π sin two π.
00:11:47.840 --> 00:11:49.740
And now, we can equate coefficients.
00:11:49.900 --> 00:11:54.410
Equating coefficients for cos of two π, we get one equals π plus π.
00:11:54.720 --> 00:11:58.440
And for sin of two π, we get negative five equals π minus π.
00:11:58.580 --> 00:12:01.790
We now have a pair of simultaneous equations in π and π.
00:12:01.990 --> 00:12:04.090
Letβs add these to eliminate π.
00:12:04.290 --> 00:12:06.930
And when we do, we get negative four equals two π.
00:12:07.270 --> 00:12:09.140
So π must be equal to negative two.
00:12:09.490 --> 00:12:11.890
And then, we substitute this back into the first equation.
00:12:12.020 --> 00:12:14.280
And we get one equals negative two plus π.
00:12:14.480 --> 00:12:15.980
So π must be equal to three.
00:12:16.520 --> 00:12:20.310
Therefore, π is equal to negative two and π is equal to three.
00:12:20.720 --> 00:12:26.100
We can of course check this by popping π equals negative two and π equals three into the other equation.
00:12:26.130 --> 00:12:30.810
When we do, we see that negative two minus three equals negative five as required.
00:12:32.210 --> 00:12:41.360
In our final example, weβre going to recall the properties of the complex conjugate and see how being able to spot the complex conjugate for numbers in exponential form can save us some time.
00:12:42.120 --> 00:12:47.840
Find the numerical value of π to the 11π by six π plus π to the negative 11π by six π.
00:12:48.560 --> 00:12:55.230
To evaluate the sum of these two complex numbers, we could convert them into algebraic form and add simply by collecting like terms.
00:12:55.470 --> 00:13:02.140
However, it is useful to be able to spot the complex conjugate of a number written in exponential form and weβll see why in a moment.
00:13:02.330 --> 00:13:10.390
For a complex number π§ equals ππ to the ππ, its conjugate denoted π§ star is ππ to the negative ππ.
00:13:10.620 --> 00:13:20.320
Notice how the modulus of the conjugate is the same as the modulus of the original complex number and that its argument is the negative of the argument of the original complex number.
00:13:20.620 --> 00:13:28.090
The two complex numbers we have π to the 11π by six π and π to the negative 11π by six π both have a modulus of one.
00:13:28.380 --> 00:13:33.290
But the argument of the second complex number is the negative argument of the first and in fact vice versa.
00:13:34.200 --> 00:13:41.680
This means that π to the negative 11π by six π is the complex conjugate for π to the 11π by six π and vice versa.
00:13:42.020 --> 00:13:43.290
But why does this help?
00:13:43.530 --> 00:13:47.200
Well, it allows us to use the rule for addition of a complex number and its conjugate.
00:13:47.360 --> 00:13:52.490
The sum of a complex number and its conjugate is equal to two times the real part of that complex number.
00:13:52.810 --> 00:13:58.250
Now, the real part of a complex number written in exponential or polar form is simply π cos π.
00:13:58.570 --> 00:14:03.010
So for our complex number, the real part is one times cos of 11π by six.
00:14:03.170 --> 00:14:11.110
And this means the sum of π to the 11π by six π and its conjugate π to the negative 11π by six π is two lots of this.
00:14:11.280 --> 00:14:13.700
Cos of 11π by six is root three over two.
00:14:13.910 --> 00:14:19.660
So two times the real part of our complex number is two times root three over two, which is simply root three.
00:14:20.160 --> 00:14:26.900
And we can see that the numerical value of π to the 11π by six π plus π to the negative 11π by six π is just root three.
00:14:28.490 --> 00:14:38.770
In this video, weβve learned that we can express a complex number in exponential form by using ππ to the ππ, where π is the modulus and π is the argument expressed in radians.
00:14:38.970 --> 00:14:45.170
And weβve seen that working with numbers in this form can help us simplify calculations, involving multiplication and division.
00:14:45.540 --> 00:14:50.170
To multiply two complex numbers, for example, we multiply their moduli and we add their arguments.
00:14:50.340 --> 00:14:56.450
And to divide two complex numbers written in exponential form, we divide their moduli and subtract their arguments.